Higher stress response and altered quality of life in schizophrenia patients with low membrane levels of docosahexaenoic acid - Adrien, Vladimir; Bosc, Nicolas; Fumat, Hugo; Tessier, Cédric; Ferreri, Florian; Mouchabac, Stéphane; Tareste, David; Nuss, Philippe (Frontiers in Psychiatry, 2023)
Schizophrenia is a severe, chronic, and heterogeneous mental disorder that affects approximately 1% of the world population. Ongoing research aims at clustering schizophrenia heterogeneity into various “biotypes” to identify subgroups of individuals displaying homogeneous symptoms, etiopathogenesis, prognosis, and treatment response. The present study is in line with this approach and focuses on a biotype partly characterized by a specific membrane lipid composition. We have examined clinical and biological data of patients with stabilized schizophrenia, including the fatty acid content of their erythrocyte membranes, in particular the omega-3 docosahexaenoic acid (DHA). Two groups of patients of similar size were identified: the DHA− group (N = 19) with a lower proportion of membrane DHA as compared to the norm in the general population, and the DHAn group (N = 18) with a normal proportion of DHA. Compared to DHAn, DHA− patients had a higher number of hospitalizations and a lower quality of life in terms of perceived health and physical health. They also exhibited significant higher interleukin-6 and cortisol blood levels. These results emphasize the importance of measuring membrane lipid and immunoinflammatory biomarkers in stabilized patients to identify a specific subgroup and optimize non-pharmacological interventions. It could also guide future research aimed at proposing specific pharmacological treatments.